Combined Pitch and Trailing Edge Flap Control for Load Mitigation of Wind Turbines - Keshan He; Liangwen Qi; Liming Zheng; Yan Chen (Energies, 2018)
Using active control methods for load mitigation in wind turbines could greatly reduce the cost of per kilowatt hour of wind power. In this work, the combined pitch and trailing edge flap control (CPFC) for load mitigation of wind turbines is investigated. The CPFC includes an individual pitch control (IPC) loop and a trailing edge flap control (TEFC) loop, which are combined by a load frequency division control algorithm. The IPC loop is mainly used to mitigate the low frequency loads, and the TEFC loop is mainly used to mitigate the high frequency loads. The CPFC adopts both an azimuth angle feed-forward and a loads feedback control strategy. The azimuth angle feed-forward control strategy should mitigate the asymmetrical loads caused by observable disturbances. and the loads feedback control strategy should decrease asymmetrical loads by closed loop control. A simulation is carried out on the joint platform of FAST and MATLAB. The simulation results show that the damage equivalent load (DEL) of blade root out-of-plane bending moment is reduced by 53.7% while using CPFC, compared to collective pitch control (CPC); and the standard deviation of blade tip out-of-plane deflection is reduced by 50.2% while using CPFC, compared to CPC. The results demonstrate that the CPFC can mitigate the fatigue loads of wind turbines as anticipated.